PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, DAN MOBILE BANKING TERHADAP KINERJA KEUANGAN PERUSAHAAN BANK - Dewa Ayu Ananda Dea Anjelina; Tuban Drijah Herawati (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), and mobile banking on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period, with Return on Assets (ROA) as the indicator of financial performance. The sample consists of 10 banking companies selected through purposive sampling, resulting in 40 observations. The data were analyzed using multiple linear regression with SPSS. The results indicate that Capital Adequacy Ratio (CAR) does not have a significant effect on ROA (Sig. = 0.604). Meanwhile, Non Performing Loan (NPL) has a negative and significant effect on ROA (Sig. = 0.000; coefficient = –0.715), while mobile banking has a positive and significant effect on ROA (Sig. = 0.003; coefficient = 3.200). The model explains 66.9% of the variation in ROA. These findings indicate that credit risk management and digital transformation play a more important role than capital adequacy in improving bank profitability during the post-pandemic recovery period.